Propionic Acid-Producing Bacteria as Provocateurs of Anxiety and Depression? [Letter] - Prescott SL; Logan AC (Neuropsychiatric Disease and Treatment)
Susan L Prescott,1–3,* Alan C Logan3,* 1School of Medicine, University of Western Australia, Perth, WA, Australia; 2Department of Family and Community Medicine, University of Maryland School of Medicine, Baltimore, MD, USA; 3Nova Institute for Health, Baltimore, MD, 21231, USA*These authors contributed equally to this workCorrespondence: Alan C Logan, Nova Institute for Health, 1407 Fleet Street, Baltimore, MD, 21231, USA, Email alanxlogan@gmail.com